A study of small and medium industries in Sarawak / Iris Syawe Seh Ling, Nicholas Amin and Yap Yin - Seh Ling, Iris Syawe; Amin, Nicholas; Yap, Yin (1990)
In the study, two sets of structured questionnaires were used. They were 'Form A’ (for agencies and institutions which provide incentives and support services for SMIs) and 'Form B' (for the manufacturing establishments in the state). 26 agencies or institutions responded to Form A and 620 establishments responded to Form B. The majority of the establishments are in Kuching (50.8%) and about one-third are located in the designated industrial estates in the state. A large majority of them belong to the Small Scale Industry whether the establishments are classified according to their existing paid-up capital or by employment size. 81% of these manufacturing establishments have less than 50 workers per establishment. Most of the establishments (70%) have existing paid-up capital of less than M$500,000. Only about 7% have paid-up capital exceeding M$2.5 million. In terms of the ownership structure of these establishments, the majority (86%) are owned privately either as private limited companies, sole proprietorships or partnerships. Eight main types of manufacturing industries have been considered of which the establishments in the Wood and Wood Products industry account for just over 25% of the total while slightly over a fifth are in the Food and Beverage industry. The entrepreneurs are mainly Chinese Sarawakians with about 4% Malays and other Bumiputras. Most of them have started as apprentices as more than a quarter of them have only received primary education while another one fifth have lower secondary education. Very few are graduates or professionals. Due to their low educational background, they tend to go for sole proprietorships, partnerships or private limited companies. Most of the entrepreneurs choose to enter business because of the good prospects, the desire to be independent and the challenge of the business world. Some also inherited the businesses. Those with longer working experiences are the ones who have worked their way up as apprentices. More than half (56.4%) of the entrepreneurs use their own savings as the main source of finance and very few (about 4%) of them have used or borrowed from government agencies.